Cerebrospinal fluid levels of chitinase 3-like 1 and neurofilament light chain predict multiple sclerosis development and disability after optic neuritis. (December 2015) - Modvig, S; Degn, M; Roed, H; Sørensen, TL; Larsson, HBW; Langkilde, AR; Frederiksen, JL; Sellebjerg, F
Background: Cerebrospinal fluid (CSF) biomarkers have been suggested to predict multiple sclerosis (MS) after clinically isolated syndromes, but studies investigating long-term prognosis are needed. Objective: To assess the predictive ability of CSF biomarkers with regard to MS development and long-term disability after optic neuritis (ON). Methods: Eighty-six patients with ON as a first demyelinating event were included retrospectively. Magnetic resonance imaging (MRI), CSF leukocytes, immunoglobulin G index and oligoclonal bands were registered. CSF levels of chitinase-3-like-1, osteopontin, neurofilament light-chain, myelin basic protein, CCL2, CXCL10, CXCL13 and matrix metalloproteinase-9 were measured by enzyme-linked immunosorbent assay. Patients were followed up after 13.6 (range 9.6–19.4) years and 81.4% were examined, including Expanded Disability Status Scale and MS functional composite evaluation. 18.6% were interviewed by phone. Cox regression, multiple regression and Spearman correlation analyses were used. Results: Forty-six (53.5%) developed clinically definite MS (CDMS) during follow-up. In a multivariate model MRI ( p =0.0001), chitinase 3-like 1 ( p =0.0033) and age ( p =0.0194) combined predicted CDMS best. Neurofilament light-chain predicted long-term disability by the multiple sclerosis severity scale ( p =0.0111) and nine-hole-peg-test ( p =0.0202). Chitinase-3-like-1 predicted long-term cognitive impairment by the paced auditory serial addition test ( p =0.0150). Conclusion: Neurofilament light-chain and chitinase-3-like-1 were significant predictors of long-term physical and cognitive disability. Furthermore, chitinase-3-like-1 predicted CDMS development. Thus, these molecules hold promise as clinically valuable biomarkers after ON as a first demyelinating event.